2019
DOI: 10.3390/economies7020042
|View full text |Cite
|
Sign up to set email alerts
|

Construction Sector Role in Gross Fixed Capital Formation: Empirical Data from Russia

Abstract: The purpose of this study was to research and understand the interrelations between the growth of gross fixed capital formation (GFCF), the volume of construction industry, supply of interindustry balance, and amount of fixed-asset investments in Russia between 2000 and 2016. The autoregressive distributed-lagged (ARDL) bound testing methodology and regression analysis were applied to evaluate the cointegration and influence of construction industry volume on gross fixed-capital formation. Empirical studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…Lucky and Kingsley found that the ratio of government expenditure to GDP, inflation rate, the ratio of government revenue to GDP and operating surplus were the significant key determinants of capital formation in Nigerian economy during the period of 1981 to 2014. Stupnikova and Sukhadolets (2019) examined the role of construction sector in gross investment decision at a macro level in Russia. The time-series data were used to explore the interrelationship between the growth of gross investment, volume of construction industry, supply of industrial balance, and amount of fixed asset investment in Russia during the period of 2006 to 2016.…”
Section: Factors Affecting Investment Decision In Nepalmentioning
confidence: 99%
“…Lucky and Kingsley found that the ratio of government expenditure to GDP, inflation rate, the ratio of government revenue to GDP and operating surplus were the significant key determinants of capital formation in Nigerian economy during the period of 1981 to 2014. Stupnikova and Sukhadolets (2019) examined the role of construction sector in gross investment decision at a macro level in Russia. The time-series data were used to explore the interrelationship between the growth of gross investment, volume of construction industry, supply of industrial balance, and amount of fixed asset investment in Russia during the period of 2006 to 2016.…”
Section: Factors Affecting Investment Decision In Nepalmentioning
confidence: 99%
“…Another reason why all nations try to encourage investment in capital goods is that it drives economic activities. Plenty of studies have corroborated the close relationship between investment in construction and regional economic growth (Stupnikova & Sukhadolets, 2019). On the other hand, it has been argued that capital investments have negative aspects since it accelerates resource use and environmental degradation (Chen & Graedel, 2015; Müller et al., 2013; Rahman & Ahmad, 2019; Södersten et al., 2018).…”
Section: Introductionmentioning
confidence: 96%
“…A substantial share of the total final demand of goods and services is constituted by GFCF both in monetary turnover and embodied resources. Infrastructure construction contributes to changing the GFCF (Stupnikova & Sukhadolets, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Public spending efficiency is considered as a crucial step towards preventing the expansion of government expenditures. Construction is a part of the aggregate demand, e.g., in the view of infrastructure requirements (Stupnikova and Sukhadolets 2019). A considerable portion of public expenditures is spent on construction investments, such as roads, railways, hospitals, educational facilities, utilities, water management structures, etc.…”
Section: Introductionmentioning
confidence: 99%